2019
DOI: 10.1038/s41598-019-54194-y
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and therapeutic effect of umbilical cord mesenchymal stem cells in inflammatory bowel disease

Abstract: Inflammatory bowel disease (IBD) is a persistent and chronic disease that is characterized by destructive gastrointestinal (GI) inflammation. Researchers are trying to identify and develop new and more effective treatments with no side effects. Acute and chronic mouse models of IBD were established using dextran sulfate sodium (DSS) solution. To evaluate the efficacy and mechanism, umbilical cord mesenchymal stem cells (UCMSCs) were obtained from Kunming (KM) mice and humans. In the chronic IBD study, the surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 41 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…Despite the poor prospects of HSCT for the treatment of IBD, IBD patients with IL-10 gene defects seem to be cured by allogeneic transplantation [ 60 ]. The MSCT can repair damaged intestinal tissues by reducing the development of intestinal inflammation in IBD patients and by improving local microcirculation in the intestine [ 61 ]. Apart from a transient fever and a minimal risk of tumorigenesis, MSCT has not shown any other significant side effects.…”
Section: Pathogenesis Of Ibd and Current Therapeutic Agentsmentioning
confidence: 99%
“…Despite the poor prospects of HSCT for the treatment of IBD, IBD patients with IL-10 gene defects seem to be cured by allogeneic transplantation [ 60 ]. The MSCT can repair damaged intestinal tissues by reducing the development of intestinal inflammation in IBD patients and by improving local microcirculation in the intestine [ 61 ]. Apart from a transient fever and a minimal risk of tumorigenesis, MSCT has not shown any other significant side effects.…”
Section: Pathogenesis Of Ibd and Current Therapeutic Agentsmentioning
confidence: 99%
“…The study of MSCs in IBD has been extensively explored, where MSCs actively ease IBD. For example, umbilical cord MSCs (ucMSCs) are commonly used in disease treatment and their transplantation (from Kunming mice and humans) can effectively protect mice from intestinal injury (152). In addition, ucMSCs can also attenuate colitis through regulating immune cells and associated cytokines.…”
Section: Characteristics Of Mscsmentioning
confidence: 99%
“…Mesenchymal stem cell treatment of IBD has been studied in many preclinical studies trials in animal models of IBD. When MSCs are injected intravenously, they can reach the site of intestinal injury and colonize the intestinal mucosa to control the development of inflammation locally, improve local microcirculation, and repair damaged tissues [ 117 ]. Studies have shown that MSC treatment of IBD is mainly carried out through local microcirculation construction, colonization and repair, and immunomodulation ( Table 3 ).…”
Section: Stem Cell Therapy For Ibdmentioning
confidence: 99%